The parting of the sea how volcanoes, earthquakes, and plagues shaped the story of Exodus - Sivertsen, Barbara J. 1949- (Princeton, NJ [u.a.] Princeton Univ. Press, 2009)
Dating the Exodus -- The coming of the Hyksos -- The Minoan eruption -- The plagues, the Exodus, and historical reality -- Moses and the mountain of God -- The sojourn in the wilderness -- Meanwhile, back in civilization -- The destruction of Jericho -- The conquest and settlement of Canaan -- Back to Egypt -- The formation of the Exodus tradition
Dating the Exodus -- The coming of the Hyksos -- The Minoan eruption -- The Plagues, the Exodus, and historical reality -- Moses and the mountain of God -- The Sojourn in the wilderness -- Meanwhile, back in civilization -- The destruction of Jericho -- The conquest and settlement of Canaan -- Back to Egypt -- The formation of the Exodus tradition
Includes bibliographical references and index
Archivierung/Langzeitarchivierung gewährleistet
Keywords: Bible and geology; Bible stories, English -- Exodus; Exodus, The